Effective bioleaching of chromium in tannery sludge with an enriched sulfur-oxidizing bacterial community. (October 2016) - Zeng, Jing; Gou, Min; Tang, Yue-Qin; Li, Guo-Ying; Sun, Zhao-Yong; Kida, Kenji
Highlights: Bioleaching of chromium in tannery sludge using an enriched microbial community. Maximum bioleaching efficiency of Cr from tannery sludge was up to 96.8%. Forms of chromium in sludge affected the bioleaching performance. Some indigenous bacteria in sludge played a supporting role in bioleaching. Abstract: In this study, a sulfur-oxidizing community was enriched from activated sludge generated in tannery wastewater treatment plants. Bioleaching of tannery sludge containing 0.9–1.2% chromium was investigated to evaluate the effectiveness of the enriched community, the effect of chromium binding forms on bioleaching efficiency, and the dominant microbes contributing to chromium bioleaching. Sludge samples inoculated with the enriched community presented 79.9–96.8% of chromium leaching efficiencies, much higher than those without the enriched community. High bioleaching efficiencies of over 95% were achieved for chromium in reducible fraction, while 60.9–97.9% were observed for chromium in oxidizable and residual fractions. Acidithiobacillus thiooxidans, the predominant bacteria in the enriched community, played an important role in bioleaching, whereas some indigenous heterotrophic species in sludge might have had a supporting role. The results indicated that A. thiooxidans -dominant enriched microbial community had high chromium bioleaching efficiency, and chromium binding forms affected the bioleaching performance.